Pengaruh Pembelajaran Berbasis Masalah melalui Metode Eksperimen Terhadap Keterampilan Proses Sains Fisika Siswa SMA Negeri 1 Selong Tahun Ajaran 2014/2015 - Dharmawan Susanto; Sutrio Sutrio; Wahyudi Wahyudi (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2015)
This study is an experimental aims to finding out the effect of problem based learning through experimental methods on studentÃ¢â¬â¢s physics science process skills of SMA Negeri 1 Selong academic year 2014/2015. The design of this study used pretest-posttest control group design, while the sampling technique used cluster random sampling. The population of this study is students of grade X Science Program SMA Negeri 1 Selong, while the samples are the students of class X 1 (experimental group) and class X 4 (control group). The instrument of this study is the science process skills test. The result data was analyzed by t-test pooled variant two tails. Obtain values thint = 5.38, ttable = 1.99 at the significance level of 5%. Because - ttable < thint > + ttable, then Ho will be rejected and Ha will be accepted which indicates that there is significant the effect of problem based learning through the experimental method on physics science process skills of students of SMA Negeri 1 Selong academic year 2014/2015.